RETRACTED: Dispersed Ag2O/Ag on CNT-Graphene Composite: An Implication for Magnificent Photoreduction and Energy Storage Applications - Mohamed, Mohamed Mokhtar; Khairy, M.; Ibrahem, Ahmed (Frontiers in Chemistry, 2018)
A simple hydrothermal route assisted by a triblock copolymer was used to synthesize Ag2O/Ag nanoparticles on a robotic support consists of functionalized MWCNTs and graphene composite (Ag2O/Ag/CNT-graphene). This composite together with the individual analogue Ag/CNT and Ag/graphene were characterized by means of XRD, TEM-SAED, N2 sorptiometry, Raman, FTIR, UV-Vis, and photoluminescence spectroscopy. These nanomaterials were then tested for the catalytic reduction of 4-nitrophenol (4-NP) to the technologically beneficial 4-aminophenol (4-AP). The Ag2O@Ag@CNT-graphene composite calcined at 400oC has shown fascinating reduction performances for 4-NP either in the dark (k= 0.014 s-1) or under visible light illumination (k= 0.039 s-1) in the presence of 5 mM NaBH4 compared to Ag/CNT (0.0112 s-1) and Ag/graphene (0.010 s-1) catalysts. This was chiefly because Ag2O@Ag@CNT-graphene comprises the highest pore volume (0.49 cm3/g) and involves three types of pores in the margin from 1.8 to 4.0 nm in front of only one modal type of pores for the rest of the catalysts and thus maximizes the adsorptive capacity of the reactants (4-NP and NaBH4). Moreover, the former composite exhibits the highest concentration of the Ag2O component as established by the adverse mentioned techniques in addition to the cyclic voltammetry proposing it's facile reaction with 4-NP along with simultaneous transfer of surface hydrogen and electrons from NaBH4 ions to produce 4-AP. The promotion of the p-n junction evaluated using Mott-schottky equation on Ag2O@Ag@CNT-graphene assisted by charges separation and surface plasmon resonance bands of Ag and Ag2O are found to be advantageous for 4-NP reduction. The latter composite delivers a specific capacitance of 355 F g-1 at 1.0 A g-1 exceeding those of Ag/CNT (230 F g-1) and Ag/graphene (185 F g-1). The EIS study establishes the high electronic conductivity of the metallic Ag and Ag2O moieties, low internal resistance of CNT-graphene as well as the marked ionic transfer facilitated by porous nature of the composite.